A breast prosthesis infection update: Two-year incidence, risk factors and management at single institution - Boustany, Ashley Nadia; Elmaraghi, Shady; Agochukwu, Nneamaka; Cloyd, Benjamin; Dugan, Adam J.; Rinker, Brian (Indian Journal of Plastic Surgery, 2018)
Background: Infection following augmentation and prosthetic-based breast reconstruction can cause significant physical and psychological distress for patients. It may delay adjuvant therapies and compromise aesthetic outcomes. The aim of this study is to identify modifiable risk factors for infection and identify common bacterial isolates to achieve optimal outcomes for patients. Methods: A retrospective cohort study was performed for patients undergoing implant-based breast reconstruction over a 2-year period. In each case, we documented demographics, co-morbidities, complications and antibiotic use. We reviewed treatments, infectious species cultured where applicable and all outcomes. Results: A total of 292 patients met the inclusion criteria. Fifty-five patients (19%) developed an infection. Univariate analysis showed a significantly increased infection rate with longer operative times (P = 0.001) and use of tissue expanders (P = 0.001). Multiple logistic regression analysis confirmed drain use and elevated body mass index (BMI) as risk factors (odds ratio [OR] 2.427 and 1.061, respectively). After controlling for BMI, smoking status and radiation, we found an increased odd of infection with allograft use (OR 1.838) and a decreased odd with skin preparation using 2% chlorhexidine gluconate in 70% isopropyl (OR 0.554), though not statistically significant. Forty of 55 patients with infections had cultures, with 62.5% of isolates being Gram-positive species and 30% Gram-negative species. The median time to clinical infection was 25 days. Implant salvage with surgical interventions was achieved in 61.5% of patients. Conclusions: This study identified judicious use of drains and efficiency in the operating room as modifiable risk factors for infections following implant-based breast reconstruction. Prospective trials to analyse techniques for infection prevention are warranted. Implant salvage following infection is a possible end-point in the appropriate patient.
Keywords: Breast implant infections; implant salvage; infection risk factors; tissue expander infections